The growing threat of antibiotic resistance in wound infections: evidence from tertiary care in Pakistan - Imran, Hassan; Khan, Zaman; Saleem, Fiza; Gull, Sidra; Tahir, Ali (Archives of Biological Sciences, 2023)
Paper description: The overall prevalence of wound infection was 53.5%. Staphylococcus aureus was the most prominent bacteria, followed by Escherichia coli. Linezolid, vancomycin and teicoplanin were the most effective antibiotics. Diversity matrices were used to quantify the uncertainty of the effectiveness of antibiotics; 129 resistance types were detected. The presence of diverse resistance types points to the need to characterize the microbial pathogens in infected wounds and analyze antibiotic susceptibility profiles prior to application of antibiotic therapy aimed at reducing the emergence and dissemination of antibiotic resistance. Abstract: The present study analyzed 361 non-duplicated wound swab samples from 187 males and 174 females, ranging in age from 0 to 100 years with a mean age of 37.1±1.9 years, and to determine the prevalence of bacterial wound infections and the diversity of antibacterial susceptibility patterns of the isolated bacteria to detect the presence of unique/rare resistance types. Of these, 53.46% (193) were found to have wound infections. Most of the infected patients fell in the age group II (21-40 years). A total of 14 bacterial species were identified, with Staphylococcus aureus and Escherichia coli being the most common Gram-positive and Gram-negative bacteria, respectively. Linezolid and vancomycin were the most effective antibiotics against the isolated Gram-positive bacteria, while most Gram-negative bacteria were sensitive against colistin and polymyxin-B. Based on antibiotic resistance, 129 types of resistance were detected. Multi-resistance was detected in 157 (81.3%) bacterial strains, while 162 strains had a multi-antibiotic resistance index (MAR) of 0.2. Simpson and Shannon diversity indices indicated high bacterial diversity in the wound samples. The study provides valuable insight into the prevalence of bacterial infections in wounds and that antibiotic resistance patterns can be useful in guiding the development of effective treatment strategies.